The Classic: New perspectives on a criticized practice - Korsvoll, Anne Guro (Nordisk Tidsskrift for Helseforskning, 2025)
The purpose of this essay is to provide new perspectives on collaboration as a fundamental skill in the nursing profession. Collaboration is something we all relate to, and one might get the impression that collaboration skills are a recurring theme in both general and higher education. As an Assistant Professor and nurse, I am witnessing and participating in collaboration daily, and in this essay, I seek a deeper understanding of the complexities inherent in this classic practice. What factors contribute to and underpin the promotion of synergy in collaboration? The essay is centered on nursing students, and I invite the reader to join me in my reflections, perspectives, and associations related to collaborative competence. The literature is drawn from a selection of philosophical, pedagogical, and nursing theories, as well as from curricula and regulations pertaining to national guidelines for nursing education.